A produção de narrativas em aulas gamificadas - Cunha, Paula Rios da (2023)
This research has as general objective to identify the way in which ninth-year elementary school students can expand their sociocultural universe in the production of narratives from gamified classes. The specific objectives are based on the subsequent actions of the proposal, they are: identify and describe how much gamification in Portuguese language classes has the potential to assist in the production of narratives; establish relationships between gamification and increased interest of students in mother tongue classes in the production activity of this genre; and, finally, demystify the use of gamification in the classroom, showing that it is possible to implement it combined with traditional activities such as textual production. Thus, it is possible to produce material relevant to future research in the area that corroborates the idea of innovation in the school environment. As for theoretical assumptions, the research is based on the concepts of chronotope and exotopy, conceived by the Russian researcher self-styled philosopher of language, Mikail Bakhtin. The methodology is based on action research. The results showed that the gamified classes did not show the expected, and, in addition to their glamorization, require more frequent applications in order to achieve satisfactory effects, since, alone in a momentary classroom context, they do not promote significant changes in the sociocultural repertoire of students.